1977
DOI: 10.1080/09553007714550521
|View full text |Cite
|
Sign up to set email alerts
|

E.S.R. of Spin-trapped Radicals in Aqueous Solutions of Amino Acids

Abstract: The radicals produced by reactions of hydroxyl radicals with amino acids in aqueous solutions have been investigated. Hydroxyl radicals were formed by U.V.-photolysis of hydrogen peroxide and the short-lived amino acid radicals were spin-trapped by tert-nitrosobutane and identified by electron spin resonance spectroscopy. Nineteen amino acids were studied, and several radicals were identified which have not been observed previously by other methods. Only side-chain radicals were identified for alanine, threoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
2
40
0
1
Order By: Relevance
“…In addition, when higher concentrations (0.1 M) of D,L-histidine are used and the reaction is carried out at pH 7, the spin adduct obtained is predominantly a triplet of doublets with hyperfine coupling constants aN = 1.57 mT and a& = 0.34 mT. These values are also consistent with previous data obtained for the spin trapping of histidyl radicals following the reaction of 'OH with histidine [24]. The results shown in fig.1 confirm that 'OH are formed at the concentrations of V02+ and Hz02 used.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, when higher concentrations (0.1 M) of D,L-histidine are used and the reaction is carried out at pH 7, the spin adduct obtained is predominantly a triplet of doublets with hyperfine coupling constants aN = 1.57 mT and a& = 0.34 mT. These values are also consistent with previous data obtained for the spin trapping of histidyl radicals following the reaction of 'OH with histidine [24]. The results shown in fig.1 confirm that 'OH are formed at the concentrations of V02+ and Hz02 used.…”
Section: Resultssupporting
confidence: 89%
“…This computer simulation was generated using hyperfine coupling values of 1.52 mT, 0.19 mT, 0.38 mT, 0.19 mT and 0.073 mT for the primary nitroxide nitrogen, the histidine nitrogen and the 3 histidine protons, respectively. These hyperfine coupling constants are consistent with the known spectral parameters for the histidyl radical adduct of MNP formed following 'OH reaction with histidine [24]. In addition, when higher concentrations (0.1 M) of D,L-histidine are used and the reaction is carried out at pH 7, the spin adduct obtained is predominantly a triplet of doublets with hyperfine coupling constants aN = 1.57 mT and a& = 0.34 mT.…”
Section: Resultssupporting
confidence: 80%
“…Possible candidates are the amino acids valine, isoleucine, leucine, threonine and proline. Data in the literature showed that MNP adducts of tertiary carbon-centred radicals with a hyperfine splitting between 16.3 and 16.7 G can be obtained on exposure of valine, leucine and isoleucine to hydroxyl radicals, generated by photolysis of H # O # [28]. Incubation of these amino acids with methaemoglobin and t-BuOOH in the presence of MNP did not give the formation of radical adducts.…”
Section: Oxidation Of Amino Acidsmentioning
confidence: 99%
“…Two radical adducts came from hydrogen abstraction from the methyl groups of each amino acid (Figures 7B and 7C). The non-equivalence in the hyperfine splitting constants of the β-protons can be explained by the presence of two asymmetrical conformers produced by internal steric hindrance ( [28], and references therein). The third species that was observed came from a tertiary carbon ( Figure 7D).…”
Section: Table 1 Hyperfine Coupling Constants Of Radical Adducts Genementioning
confidence: 99%
“…Among spin trapping studies, 2-methyl-2-nitrosopropane (MNP) has been utilized as one of the most informative spin traps (1)(2)(3)(4)(5). However, it is known that when the method of spin trapping with MNP is applied to y-radiolysis in aqueous solutions, esr spectra obtained are often too complicated to be analyzed accurately.…”
Section: Introductionmentioning
confidence: 99%